Single-cell RNA sequencing reveals heterogeneity of mucosa-associated invariant T cells in donor grafts and its diagnostic relevance in gastrointestinal graft-versus-host disease - Mengge Gao; Kainan Zhang; Siqi Li; Huidong Guo; Yuqian Sun; Jun Kong; Tingting Han; Yingjun Chang; Xiaojun Huang; Xiaosu Zhao (Haematologica)
Granulocyte colony-stimulating factor (G-CSF) enhances acute graft-versus-host disease (aGVHD) prophylaxis in allogeneic hematopoietic stem cell transplantation (allo-HSCT) by inducing T cell tolerance and altering graft cell composition. Previous studies have shown that the number of mucosa-associated invariant T (MAIT) cells in G-CSF induced graft was associated with a low incidence of gut aGVHD. However, the effect of G-CSF mobilization on MAIT cell and its role in MAIT-mediated protection against gut GVHD remain unclear. Here, using single-cell RNA sequencing (scRNA-seq), we found that the interaction of G-CSF with its receptor CSF3R enhances of immunosuppression and tissue repair functions of MAIT cells, contributing to the anti-gut aGVHD effect. The chemokine receptor CXCR6 was identified as potentially crucial for recruiting these functional MAIT cells to gut tissues. Besides, we simulated the dynamic distribution of MAIT cells from donor GCSF mobilized peripheral blood stem cells (G-PBSCs) grafts in recipient mouse, and further confirmed that the circulating MAIT cells migrated into gut tissue in a CXCR6-CXCL16 dependent manner. To further validate these findings, we developed a flow cytometry panel that effectively predicts the gut aGVHD occurrence following allo-HSCT by analyzing the frequency and functional markers of MAIT cells in G-PBSCs. The predictive model shifts aGVHD prediction and intervention to the pre-transplant stage and offers a new strategy for the prevention and management of gut aGVHD in clinical practice.